From an Index to Anna Akhmatova’s Notebooks: Tomas Venclova - Timenchik, Roman (Literatūra, 2025)
The note continues a series of more than fifty publications that provide detailed commentary on the names of individuals recorded in Anna Akhmatova’s working notebooks. It analyzes the topics of Akhmatova’s conversations with the poet and translator of her poems into Lithuanian, Tomas Venclova. These conversations concern Akhmatova’s book of poems published in Lithuania in 1964, as well as Lithuanian poets and translators – both those documented in the notebooks and those presumably known to Akhmatova. A recurring topic of their discussions was the episode of Akhmatova’s and Nikolai Gumilyov’s brief stay in Vilnius in December 1914. In Venclova’s memoirs, we find Akhmatova’s remarks on Ivan Bunin’s Nobel lecture, selected poems by Osip Mandelstam, and the composer Andrei Volkonsky. The note also clarifies the identity of the ‘hero’ of one of Akhmatova’s favorite oral stories, which is likewise recorded in her Lithuanian interlocutor’s recollections.
Keywords: Lithuanian translations of Anna Akhmatova; Tomas Venclova; Vincas Mykolaitis-Putinas; Osip Mandelstam; Nobel Prize in Literature; Ivan Bunin; Gabriel Superfin